PENINGKATAN MOTIVASI BELAJAR FISIKA MELALUI PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN PENDEKATAN MULTI KECERDASAN DI SMA NEGERI I KAMPAR - Zuhdi Ma’aruf; Muhammad Sahal; Desi Susanti (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2007)
The purpose of this research was to find improvement the student physics learning motivation in teaching physics through applying quantum teaching by multi intelegences approach implementation by the first year students at SMA N 1 Kampar on academic year 2005/2006. Improvement learning motivation is seen 15 learning motivation indicators. The subject of the research is the student X3 class of SMA N 1 Kampar the sample taken was 37 student. Research instrument used of collecting data in this research is questioner first motivation and questioner end motivation. The student motivation data analysis by descriptive analysis and differential analysis. The descriptive analysis showed that : (1) The motivation student learning as the topic rectiliniear motion through applying quantum teaching by multi intelegences approach implementation is categorized high and (2) Improvement the student physics learning motivation through applying quantum teaching by multi intelegences approach implementation 16,2 %.